2021
DOI: 10.3390/en14196015
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Building-Integrated Photovoltaics (BIPV) to the Concept of Nearly Zero-Energy Cities in Europe: Potential and Challenges Ahead

Abstract: The main purpose of this paper is to investigate the contributions of building-integrated photovoltaic (BIPV) systems to the notion of nearly zero-energy cities in the capitals of the European Union member states (EU), Norway, and Switzerland. Moreover, an in-depth investigation of the barriers and challenges ahead of the widespread rollout of BIPV technology is undertaken. This study investigates the scalability of the nearly zero-energy concept using BIPV technology in moving from individual buildings to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Examples, ie Powerhouse Brattørkaia (NO), Umwelt Arena (CH) or Copenhagen International School (DK) discussed by Devetaković et al [15] confirm much wider formal and colour possibilities of photovoltaic systems that can be used on facades. BIPV Systems such as tiles, modules, glazing or foil offer wide possibilities of harmonious design of Building-Integrated Photovoltaics [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples, ie Powerhouse Brattørkaia (NO), Umwelt Arena (CH) or Copenhagen International School (DK) discussed by Devetaković et al [15] confirm much wider formal and colour possibilities of photovoltaic systems that can be used on facades. BIPV Systems such as tiles, modules, glazing or foil offer wide possibilities of harmonious design of Building-Integrated Photovoltaics [10].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the architectural integration of PV panels in building facades presented significant economic and ecologic advantages, however the main difficulty of the integration of active solar systems on building facades derived from technical limitations like overshadowing. Contribution, potential and future challenges of building-integrated photovoltaics (BIPV) to the concept of nearly zero-energy cities in Europe were analised by Gholami, Rostvik and Steemers [10]. Tsoumanis et al [11] studied the smart evolution of historical cities in context of using photovoltaics while respecting cultural heritage.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive study conducted by [16] on the "contribution of BIPV to the concept of Nearly Zero Energy cities in Europe: Potential and Challenges ahead", the foreseeable limitations to the adoption of BIPVs in Europe are discussed in depth. The study highlights the possibility of scaling up BIPV projects from individual buildings to bigger cities.…”
Section: Summary Of Publicationsmentioning
confidence: 99%
“…Currently, there are no BIPV specific rules, regulations, and policies in most countries [8]. BIPV must comply with building codes as well as the electrical codes with assured structural strength and fire safety [18,19]. Since these rules are not clearly defined for BIPV projects, confusions may happen which could limit the trust and confidence of the building and PV stakeholders.…”
Section: Lack Of Stakeholder Trustmentioning
confidence: 99%